Is It Possible to Simplify Risk Stratification Scores for Patients with ST-Segment Elevation Myocardial Infarction Undergoing Primary Angioplasty? - Timóteo, AT (2014)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2014-04-16T09:12:08Z No. of bitstreams: 1 RPC 2013 967.pdf: 662874 bytes, checksum: 14f9a84e7a98821e1fef8655f30a2793 (MD5)